2017
DOI: 10.3389/fgene.2017.00130
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and Prolonged Infections in a Child with a Homozygous IFIH1 Nonsense Mutation

Abstract: In an Egyptian girl born to consanguineous parents, whole-exome sequencing (WES) identified a homozygous mutation in PHGDH, c.1273G>A (p.Val425Met), indicating 3-phosphoglycerate dehydrogenase deficiency. This diagnosis was compatible with the patient’s microcephaly, severe psychomotor retardation, seizures and cataracts. However, she additionally suffered from recurrent (at least monthly) episodes of prolonged and severe chest infections requiring hospitalization, suggesting a secondary, predisposing and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…No further rhinovirus infections or IAV infections have been reported in this patient to date (Asgari et al 2017). The third patient suffered from recurrent severe upper and lower respiratory tract/chest infections requiring frequent hospitalization and intensive care, although the viral pathogen was not identified from her nasal swabs (Zaki et al 2017). Thus, one of the three individuals with homozygous LOF MDA5 deficiency has suffered from severe influenza infections.…”
Section: Ieis Causing Defective Type I and Iii Ifn Responses That Havmentioning
confidence: 83%
See 2 more Smart Citations
“…No further rhinovirus infections or IAV infections have been reported in this patient to date (Asgari et al 2017). The third patient suffered from recurrent severe upper and lower respiratory tract/chest infections requiring frequent hospitalization and intensive care, although the viral pathogen was not identified from her nasal swabs (Zaki et al 2017). Thus, one of the three individuals with homozygous LOF MDA5 deficiency has suffered from severe influenza infections.…”
Section: Ieis Causing Defective Type I and Iii Ifn Responses That Havmentioning
confidence: 83%
“…Two of the 11 individuals (including parents of the index patients) carrying heterozygous LOF IFIH1 mutations reported by Asgari et al suffered from severe rhinovirus infections and 5 suffered from severe RSV infections (Asgari et al 2017). However, the heterozygous parents and siblings of the three reported homozygous patients are clinically healthy (Asgari et al 2017;Lamborn et al 2017;Zaki et al 2017). The probability of being loss-of-function intolerant (pLI) for IFIH1 is 0 (o/e = 1.25), which suggests that heterozygous LOF mutations of this gene would be tolerated in the general population.…”
Section: Ieis Causing Defective Type I and Iii Ifn Responses That Havmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, 3-phosphoserine is converted to Lserine by PSP [24]. L-serine is an important precursor involved in various processes, such as synthesis of proteins and phospholipids as well as the synthesis of tetrahydrofolate metabolites and speci c amino acids, namely glycine, cysteine and D-serine [25,26]. Previous studies have shown that L-serine supplementation can attenuate alcoholic fatty liver formation in mice and rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the induction of protection against these viruses, MDA5 senses long fragments of cytosolic dsDNA, leading to the production of type I IFNs and pro-inflammatory IL-1 family of cytokines 78,79 . Several LOF mutations in IFH1, encoding MDA5, have been reported in patients suffering from severe respiratory viral infections [80][81][82] (Table 1). These mutations impaired downstream IFN signaling and led to defective control of HRV replication in vitro 80,81 .…”
Section: Recent Insights Gained From Primary Immunodeficiency Disordementioning
confidence: 99%